New generalizations of the Poisson Kernel. (1997) - Haruki, Hiroshi; Rassias, Themistocles M.
Abstract : The purpose of this paper is to give new generalizations of the Poisson Kernel in two dimensions and discuss integral formulas for them. This paper concludes with an open problem.